Micro model analysis of JD6 and JD7 Eindhoven walls with fixed smeared crack model - Karaton, Muhammet; Çanakçı, Kağan (My University, 2020)
Micro, simplified micro and macro modelling are used for the numerical modeling of the masonry. In thisstudy, the efficiency of a 3-dimensional fixed smeared crack model in the micro modelling of masonry wallsis investigated. For this purpose, the experimental results of the masonry walls called as the JD6 and JD7Eindhoven walls are selected. The concrete model with three parameters which special case of WilliamWarnke model is used to calculate the nonlinear behavior of mortar and brick regions of this wall. Interfaceelement is not use at between brick and mortar. Predictor-corrector technique used for nonlinear analysis.Numerical and experimental results are compared in terms of the base shear-peak displacement curve andthe crack regions obtained in the walls. Good approximation are obtained between experimental andnumerical results with regard to ultimate base-shear force obtained. Some differences are determinedbetween experimental and numerical results with regard to threshold displacement value that calculatedversus ultimate base-shear force.
Keywords: İnşaat Mühendisliği; İnşaat ve Yapı Teknolojisi